Real-Time Settlement Readiness for a Future T+0 Market Structure - Pavana Kumar Chandana (Malikussaleh University, Aceh, Indonesia, 2026)
The progressive compression of securities settlement cycles from T+5 to T+2, T+1, and ultimately the aspirational T+0 real-time settlement represents a fundamental transformation in modern financial market infrastructure. This evolution has been driven by regulatory reforms, advances in digital technologies, and the need to mitigate systemic vulnerabilities exposed during major financial crises. However, most existing post-trade infrastructures remain dependent on batch-oriented architectures that were designed for longer settlement cycles and are therefore unable to support the speed, scalability, and resilience required for real-time settlement environments. This study examines the architectural and operational requirements necessary to enable T+0 settlement through event-driven, cloud-native financial infrastructures. The proposed architecture integrates microservices, high-throughput messaging platforms, distributed processing, and automated operational workflows to support continuous, low-latency transaction processing with minimal downtime. In addition, the study emphasizes the importance of pre-trade readiness frameworks, intelligent exception management, and machine learning–driven decision support to replace the manual and interval-based operational processes commonly found in legacy T+2 settlement systems. While T+0 settlement significantly reduces counterparty credit exposure and settlement risk, it simultaneously introduces new operational, cybersecurity, and liquidity challenges due to compressed processing windows and increased dependence on real-time infrastructure. Furthermore, the study highlights that the benefits of T+0 settlement are influenced by market network topology. In particular, scale-free financial networks may derive fewer advantages from real-time settlement than traditionally interconnected markets, thereby affecting the effectiveness of central counterparty clearing mechanisms. The findings suggest that successful implementation of T+0 settlement requires more than technological modernization. It also demands coordinated regulatory reform, industry-wide infrastructure standardization, interoperable data governance, and carefully planned transition strategies that enable both large financial institutions and smaller market participants to adopt real-time settlement capabilities while maintaining financial stability, operational resilience, and long-term market efficiency